THE ROLE OF ISLAMIC SOCIAL FINANCE IN EMPOWERING YOUTH AND WOMEN IN SOKOTO STATE OF NIGERIA - Muhammad, Aliyu Dahiru; Maidoki, Muhammad Lawal; Sani, Usman Buhari (Bank Indonesia, 2018)
Islamic Social finance is an emerging area of study and practice, different from commercial finance. It concerns about financing members of the community or country for socio-economic development. However, it faces the challenge of sustainability either due to legal or regulatory framework or due to lack of awareness among members of the society. The history of Islamic social finance in Nigeria connects back to the revivalism of Islam through Shehu Uthman Bin Fodio in 1804. Recently, with the establishment of Zakat and Endowment Committee in Sokoto in 2007, there was an increasing awareness and practice in the contemporary Islamic Social Finance, especially when the Government converts the Committee into Commission in 2016 which makes it independence to initiate and execute its policies. The objective of this paper is to examine two of its recently executed projects vis-à-vis Youth and Women Empowerment programs. The study uses qualitative technique for data collection and analysis. Two focus group sessions were conducted with the Youth and Women entrepreneurs who benefitted from the empowerment programs by the SZEC. The study finds that the Youth have been able to harness their potentials by expanding their businesses and upgrading the quality of their products and services such as shoe repair due the skills acquired in the training. Moreover, the women have improved their welfare and that of their children to an unprecedented level. They were able to maintain their chosen business as livelihood of income. However, they reveal that, marketing of their finished products is the major challenge they face.